Control of the Chamber in Extra-Thick Coal Seam Based on Fracture Characteristics of Coal Rock and Mass - Yang Tai; Guozhi Lu; Hongchun Xia; Jinrong Liu; Yanqun Zhang (Advances in Civil Engineering)
As the development characteristics of cracks of the chamber are closely related to the bolt and cable anchoring parameters, the original rock stress of the surrounding rock, and fracture degree, this paper proposes the control method for chamber in extra-thick coal seam by the crack development characteristics. Based on the numerical model analysis, the chamber generates a large amount of shear cracks. Then, these cracks further extend and expand. When the cracks penetrate each other, the chamber bearing capacity decreases sharply, and the corresponding displacement also increases significantly. Based on the above rules, a chamber control method by high-strength anchor bolts and grouting reinforcement is proposed to improve the rock shear strength. By optimizing the anchor bolt parameters and grouting parameters, such as spacing, length, and the grouting pressure, the cracks are significantly reduced and the cracks are prevented from penetrating. Finally, an industrial test was conducted in the chamber at Datong Coal Group, and the chamber deformation was well controlled.